(untitled) (Current Horticulture, 2024)
The field experiment was conducted on taro (Colocasia esculenta L. Schott) during 2017, 2018 and 2019 with three spells of irrigation (irrigation for 2 months and remaining period under stress, irrigation for 4 months and remaining period under stress, irrigation for 6 months) and four levels of drip irrigation, viz. 75%, 100%, 125% and 150% of water requirement of the crop (ETc) in factorial design. Pooled analysis of three years data revealed significant difference in growth and yield as well as water-use efficiency under stress and non-stress conditions. Moisture stress two and four months after planting resulted in reduction in leaf area index (-21 and -19%), number of tillers ( -27 and -6%), root to shoot ratio (-60 and -43%), cormel to corm ratio (-69 and -53%), cormel yield (-58 and -28%), water-use efficiency (-32 and -36%) and increase in corm yield (+34 and +52%) respectively, compared to no stress. Drip irrigation for six months @ 100% ETc recorded optimum growth, cormel yield (21.08 tonnes/ha) with water-use efficiency (0.4 g/L) in upland condtion.